Bacteria as potential biocontrol agents for managing purple witchweed (Striga hermonthica) in grain sorghum - Osman, Nadia Yasseen; Ahmad-Hamdani, Muhammad Saiful; Oslan, Siti Nurbaya; Mohamed Zulperi, Dzarifah; Mohd Hashim, Amalia; Saidi, Noor Baity (Cambridge University Press, 2024)
Purple witchweed [Striga hermonthica (Delile) Benth.], a highly destructive parasitic weed, poses a significant threat to sorghum [Sorghum bicolor (L.) Moench] cultivation. This hemiparasitic plant intrudes its root system into the host plant, leading to substantial yield losses, particularly in susceptible genotypes. In the pursuit of eco-friendly solutions, the biocontrol approach has gained attention as a potential management strategy for Striga. In this study, 13 bacterial strains belonging to the genera Bacillus, Gluconobacter, Pseudomonas, and Streptomyces were investigated in vitro for their efficiency in controlling the early-stage development of Striga. Among the tested strains, Streptomyces morookaensis NRRL B-12429 demonstrated significant inhibition of Striga seed germination and radicle elongation at 54.36% and 61.84%, respectively, when applied to preconditioned seeds with a synthetic germination stimulant. The effect of S. morookaensis on the inhibition of Striga seed germination was more pronounced in the presence of the host plant, sorghum, at 62.35%. However, biopriming of sorghum seeds with S. morookaensis did not enhance the inhibitory effects on Striga seed germination but resulted in a greater reduction in radicle elongation at 74.64% compared with non-primed seeds. Additionally, the biopriming with S. morookaensis promoted the growth of shoots and roots of germinating sorghum, regardless of the presence of Striga seeds. These findings highlight the potential of S. morookaensis strain NRRL B-12429 as a viable candidate for biocontrol agent applications in sorghum cultivation. Further exploration and investigation of its biocontrol capabilities can provide valuable insights for sustainable management practices against Striga infestations.